Investigation of Sheng Mai Yin in the treatment of anthracycline-induced frequent premature ventricular contractions in cancer patients: study protocol for a multicenter, randomized, double-blind, placebo-controlled clinical trial - Yang, Qiwen; Niu, Chaofeng; Li, Meng; Wang, Tangshun; Wang, Ce; Han, Longzhen; Wei, Lan; Zhang, Yayue; Li, Dong; Yi, Shuhua; Wang, Duolao; Zhang, Lijing (Frontiers in Cardiovascular Medicine, 2025)
IntroductionAnthracycline-induced cardiotoxicity is a major concern in cancer treatment, as it can lead to various arrhythmias, with frequent premature ventricular contractions (PVCs) being one of the most common types. Sheng Mai Yin (SMY), a widely used Chinese herbal compound in China, has shown potential in treating anthracycline-induced cardiac dysfunction and arrhythmias. However, the evidence supporting its efficacy is limited due to methodological flaws in prior studies. Therefore, high-quality trials are essential to rigorously evaluate the efficacy and safety of SMY.MethodsThis multicenter, randomized, double-blind, placebo-controlled trial will assess the efficacy and safety of SMY in treating frequent PVCs induced by anthracycline chemotherapy. A total of 212 patients with breast cancer or malignant lymphoma undergoing anthracycline-based chemotherapy, who have been diagnosed with new-onset frequent PVCs and Qi and Yin deficiency syndrome, will be enrolled. Participants will be randomly assigned to receive either SMY or a placebo for 8 weeks, alongside standard medications. The primary outcome is the reduction rate in PVC frequency. Secondary outcomes include PVC symptom scores, Traditional Chinese Medicine syndrome scores, cardiac dysfunction biomarkers, and major adverse cardiovascular events.DiscussionThe results of this trial are expected to provide robust evidence regarding the efficacy and safety of SMY in the treatment of anthracycline-induced frequent PVCs.Trial registrationhttp://itmctr.ccebtcm.org.cn. Registration number: ITMCTR2024000858.